Effective monetary policy, banks’ pricing behaviour and human development in Africa - Iddrisu, A.G.; Abor, J.Y.; Andani, A. (International Journal of Banking Accounting and Finance, 2022)
This paper empirically examines the effect of monetary policy effectiveness on human development in Africa. We employ both micro-bank level and macro-country-level data. Bank-level data is taken from the bank scope database maintained by Fitch, IBCA, and Bureau Van Dijk. Series are yearly, covering a sample of 320 banks across 29 African countries. Panel fixed effects, random effects and IV regressions were estimated for the period 2002 to 2013. For our IV estimation, the paper explores an instrumental variable based on the fact that effective monetary policy is conditional on the independence of the central bank. The regression results that ensued suggest that first, effective monetary policy translates to high banks’ loan and deposit prices. Building on these results and employing various specifications of banks’ pricing strategy, the second test suggests that high banks’ pricing induced by effective monetary policy tends to increase human development. Results of the net effects eventually suggest that effective monetary policy, overall, does not improve human development.
Research Article
Keywords: effective monetary policy; banks’ pricing; human development